KEABSAHAN KUASA JUAL DALAM PENGIKATAN PERJANJIAN JUAL BELI TANAH - Bella Bretyaning Danaparamita; Maudy Fadhilah (Hang Tuah Law Journal, 2021)
Soil is very important for human life. PPJB and the law of sale as regulated in 1338 of the Civil Code which are free to contract, do not violate the law, power and ethics, and apply to both buyers and sellers (the parties). In fact, it often happens in PPJB and the selling power is carried out several times or in stages. In the registration of PPJB certificates and sales capacity, not all land agencies can accept them. This study focuses on the validity of the selling rights in the songs of land rights and the legal consequences of court decisions. This research adopts a normative legal research method. The reason for choosing this method is because laws and regulations are used as the main material for analysis. The results of the study indicate that the use of power of attorney on PPJB land is legal and does not need laws and regulations, but is still needed to avoid absolutes and local court decisions. If it has a permanent legal effect, it can be made into the basic music of land rights, in the land book and transferred back, and a certificate is issued in the name of the buyer as the last right holder.